SYSTEMATIC REVIEW OF HERBAL MEDICINES USE IN PREGNANCY - O.V. Reshet'ko; K.A. Lutsevich; N.V. Gorshkova; O.V. Yakovleva (Union of pediatricians of Russia, 2011)
Data on the prevalence use of herbal remedies during pregnancy were obtained from systematic review of 25 epidemiological studies. The widespread use of herbal drugs during pregnancy indicates an increased need for documentation about its safety in pregnancy. It is necessary for healthcare personnel to discuss the use of herbal drugs with their pregnant patients. In addition, the prevalence of concomitant herbal medicines and prescribed medications use during pregnancy, and the most frequent adverse interactions suggest monitoring of reproductively safety and management risks of pharmacotherapy at obstetrics practice.Key words: herbal medicines, pregnancy, safety, review.